Video coding concepts - Richardson, Iain E (The H.264 Advanced Video Compression Standard, 2011)
This chapter contains sections titled: Introduction Video CODEC Prediction model Image model Entropy coder The hybrid DPCM/DCT video CODEC model Summary References